Strategi Meningkatkan Minat Belajar Siswa dengan Kompetensi Pedagogik dan Inovasi Guru di SD Negeri 74 Palembang - Sri Suzanah; Alhadi Yan Putra; Nuril Furkan (CV. ULIL ALBAB CORP, 2025)
This study aims to describe and analyze strategies for increasing students' learning interest through the implementation of pedagogical competence and teachers' learning innovations, as well as to analyze their impact on student achievement, the obstacles faced, and the efforts to overcome them at SD Negeri 74 Palembang. This research is a qualitative study with a case study approach. It was conducted at SD Negeri 74 Palembang with respondents including the principal, school supervisors, teachers, students, and parents. Data collection techniques included interviews, observation, and documentation. Data analysis was carried out using a qualitative method with stages such as data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the strategy to increase students' learning interest at SD Negeri 74 Palembang is implemented through the application of pedagogical competence and learning innovations by teachers. Teachers employ approaches tailored to students' needs, such as project-based learning, edutainment, and digital media, and actively participate in training. Learning innovations include the use of technology, educational games, and interactive activities such as character-building programs and extracurriculars. Supporting factors include a conducive learning environment, school support, and parental involvement. Obstacles include limited time, varying teacher competencies in technology use, students' economic conditions, and lack of parental support at home. As a result, students have become more active, confident, and successful in both academic and non-academic areas.